2012
DOI: 10.1007/s11103-012-9977-z
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of a mature plastoglobulin/fibrillin fusion protein to chloroplast plastoglobules and thylakoids in transplastomic tobacco plants

Abstract: Plastoglobules (PG) are lipid droplets in chloroplasts and other plastid types having important functions in lipid metabolism. Plastoglobulins (PGL) also known as fibrillins (FBN) are evolutionary conserved proteins present at the PG surface but also to various extents at the thylakoid membrane. PGLs are thought to have structural functions in PG formation and maintenance. The targeting of an Arabidopsis PGL (PGL34) to PG required the full protein sequence with the exception of a short C-terminal stretch. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
1
33
0
1
Order By: Relevance
“…Except of changes in the occurrence of numerous plastoglobuli in the plastid, no other significant anatomical changes were observed. Plastoglobuli are the plastidial compartment storing lipids that were found in some higher plants to be increased during TAG accumulation and adhered to thylakoid membranes [4144]. The findings suggested the existence of plastidial located TAG synthesis which resulted in the TAG accumulation in the plastid.…”
Section: Resultsmentioning
confidence: 99%
“…Except of changes in the occurrence of numerous plastoglobuli in the plastid, no other significant anatomical changes were observed. Plastoglobuli are the plastidial compartment storing lipids that were found in some higher plants to be increased during TAG accumulation and adhered to thylakoid membranes [4144]. The findings suggested the existence of plastidial located TAG synthesis which resulted in the TAG accumulation in the plastid.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding FBN distribution between PG and thylakoids, Lundquist et al have suggested that the intrinsic hydrophobicity and isoelectric point of FBN influence their localization to PG [20]. Moreover, it was demonstrated that the nearly entire sequence of FBN7a [147] or FBN1a [148] is required to target recombinant proteins to PG. Lipid remodeling requires molecular communication between PG and thylakoids that with great likelihood implicate their contact sites.…”
Section: Resultsmentioning
confidence: 99%
“…As P24 is expected to be a crucial component of any future AIDS vaccine (Obregon et al 2006 ), enormous efforts have been undertaken to develop expression strategies for the high-yield and cost-effective production of recombinant P24 protein (Meyers et al 2008 ). Proof-of-concept studies in tobacco have shown that the protein can be expressed from the nuclear genome of plants (Zhang et al 2002 ; Obregon et al 2006 ) and, much more efficiently, from the plastid genome (Zhou et al 2008 ; McCabe et al 2008 ; Shanmugabalaji et al 2013 ). Importantly, several immunogenicity studies with tobacco-derived P24 protein demonstrated elicitation of T cell responses in experimental animals (e.g., Meyers et al 2008 ; Gonzalez-Rabade et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%